A quiet language: Translating vernacular architecture for future needs - Friman, Ida (My University, 2025)
With the continued development of universal tools and construction techniques, one could argue that architecture more and more tends to become a consumer product. Previously, towns had distinctive regional and cultural characteristics which was a result of peoples direct understanding of the place they inhabited, something that has tended to be lost the further one goes into modern society. Critical regionalism, with the architect Kenneth Frampton in the forefront, advocated for an alternative approach. As to instead negotiate architectural progress through the peculiarities of a specific place. Which highlights the architects need for sensitivity to the existing conditions of the place. The thesis in turn adopts a design method that aims to explore the translation of vernacular architecture, in order to approach critical regionalism and explore its spectrum of embeddedness and contemporaneity, when dealing with new construction. Sikhall, a rural area in Dalsland, acts as the test bed for these explorations. It has had a long history of both prosperity and hardship and has thus cemented itself as a significant place in the local region. The design method builds upon literary studies, site visits, drawings, collages, digital reconstructions and design explorations through translation. The digital reconstructions summarized the survey regarding the vernacular architecture which acted as the base for the analysis before the translations could take place. The result is a proposal for a revitalized area with a new program building upon Sikhalls historical context, as well as the addition of a new flexible communal building. Deriving from the translations of the local vernacular architecture. Containing a café and exhibition space. The open ended method of translation presents many opportunities depending on the interpretations of the translator. And puts the relation between the copy and the original at the forefront, as a project could lean towards one side or the other depending on the context. The discussion whether there is an optimal position on the embeddedness and contemporaneity scale highlights the complexity of the method, as well as the needed sensitivity towards the context of every project. As it is in the translation that new compositions could be discovered.
Keywords: Critical regionalism, vernacular architecture, translation